FRI0513 The impact of depression, anxiety and fatigue in patients with behÇet's disease. (12th June 2018) - Can Sandikci, S.; Colak, S.; Omma, A.; Enecik, M.E.
Abstract : Background: Behçet's disease (BD) is a type of systemic vasculitis and inflammatory disease with unknown etiology which is associated with fatigue and lower quality of life (QoL). 1 Objectives: In this study we aimed to assess the relationship between BDCAF and BDQoL, depression, anxiety and fatigue in Behçet's disease. Methods: This is a cross-sectional study of 155 Behcet's syndrome (BS) patients and 107 healthy controls in Turkey. All subjects completed the Multidimensional Assessment of Fatigue (MAF) questionnaire, Hospital Anxiety and Depression (HADS) scale. Disease activity among BS patients was assessed using the Behçet's Disease Current Activity Form (BDCAF), and the physician's global assessment (PGA). And BD patients completed the Behçet's Disease Quality of Life (BDQoL) questionnaire. Results: There was no significant difference with age and gender between the groups. BS patients had significantly higher HADS-anxiety (HADS-A), HADS-depression (HADS-D) and MAF scores than the healthy controls (p<0.05) (table 1). BS patients with active disease had significantly higher MAF and HADS-A scores compared to inactive BS patients (p<0.05). MAF scores showed positive correlations with HADS-A, HADS-D, BDCAF and BDQoL (table 2). Conclusions: Fatigue and anxiety is common in clinically active BS patients compared with healthy controls and inactive BD patients. Reference: [1] Tascilar NF, Tekin NS, Ankarali H, et al. Sleep disorders in Behcet's disease, and their relationship with fatigue and quality of life. J Sleep Res2012;21(3):281–288. Disclosure of Interest: None declared